Montreal Cognitive Assessment and Modified Mini Mental State Examination in African Americans - Kaycee M. Sink; Suzanne Craft; S. Carrie Smith; Joseph A. Maldjian; Donald W. Bowden; Jianzhao Xu; Barry I. Freedman; Jasmin Divers (Journal of Aging Research)
Background. Sparse data limit the interpretation of Montreal Cognitive Assessment (MoCA) scores, particularly in minority populations. Additionally, there are no published data on how MoCA scores compare to the widely used Modified Mini Mental State Examination (3MSE). We provide performance data on the MoCA in a large cohort of African Americans and compare 3MSE and MoCA scores, providing a “crosswalk” for interpreting scores. Methods. Five hundred and thirty African Americans with type 2 diabetes were enrolled in African American-Diabetes Heart Study-MIND, a cross-sectional study of cognition and structural and functional brain imaging. After excluding participants with possible cognitive impairment (n=115), mean (SD) MoCA and 3MSE scores are presented stratified by age and education. Results. Participant mean age was 58.2 years (range: 35-83); 61% were female; and 64.9% had >12 years of education. Mean (SD) 3MSE and MoCA scores were 86.9 (8.2) and 19.8 (3.8), respectively. 93.5% of the cohort had a “positive” screen on the MoCA, scoring <26 (education-adjusted), compared with 47.5% on the 3MSE (cut-point < 88). A 3MSE score of 88 corresponded to a MoCA score of 20 in this population. Conclusion. The present data suggest the need for caution when applying proposed MoCA cutoffs to African Americans.